Bactericidal activities and post-antibiotic effects of ofloxacin and ceftriaxone against drug-resistant Salmonella enterica serovar Typhi. (28th June 2021) - Wain, John; Simpson, Julie A; Thi Diem Nga, Luong; Song Diep, To; Thanh Duy, Pham; Baker, Stephen; Day, Nicholas P J; White, Nicholas J; Parry, Christopher M
Abstract: Background: The clinical response to ceftriaxone in patients with typhoid fever is significantly slower than with ofloxacin, despite infection with Salmonella enterica serovar Typhi ( S. Typhi) isolates with similar susceptibilities (MIC 0.03–0.12 mg/L). The response to ofloxacin is slower if the isolate has intermediate susceptibility (MIC 0.25–1.0 mg/L). Objectives: To determine the bactericidal activity and post-antibiotic effect (PAE) of ceftriaxone and ofloxacin against S. Typhi. Methods: The mean time to reach a 99.9% reduction in log10 count (bactericidal activity) and PAE of ceftriaxone and ofloxacin were determined for 18 clinical isolates of S. Typhi in time–kill experiments (MIC range for ofloxacin 0.06–1.0 mg/L and for ceftriaxone 0.03–0.12 mg/L). Results: The mean (SD) bactericidal activity of ofloxacin was 33.1 (15.2) min and 384.4 (60) min for ceftriaxone. After a 30 min exposure to ofloxacin, the mean (SD) duration of PAE was 154.7 (52.6) min. There was no detectable PAE after 1 h of exposure to ceftriaxone. For ofloxacin, bactericidal activity and PAE did not significantly differ between isolates with full or intermediate susceptibility provided ofloxacin concentrations were maintained at 4×MIC. Conclusions: Infections with S. Typhi with intermediate ofloxacin susceptibility may respond to doses that maintain ofloxacin concentrations at 4×MIC at the site of infection. The slow bactericidal activity of ceftriaxone and absent PAE may explain the slow clinical response in typhoid.